MANAGEMENT OF GRADE II HYPERTENSION AND NYHA GRADE II HEART FAILURE IN ELDERLY WOMEN WITH LACK FAMILY - Maisuri, Ressi Ana (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Hypertension is increasing of blood pressure with advance development to the target organs damaging, such as stroke, and coronary artery disease. This disease has become unsolving problem not only in Indonesia but in worldwide too. Mrs. S, 63 years old, BP 180 / 100mmHg, HR 98x / min, 22x RR / min and T 36.6 °C, had a history of hypertension since 10 years ago and diagnosed with heart failure in 2009. Other risk factors identified in the development of hypertension in these elderly patients. The clinical diagnosis of the patients according to the JNC 7 and NYHA classification was grade II hypertension with NYHA grade II heart failure. The management was given captopril 2x12,5mg; paracetamol 3x500mg as well as a good education to patients and families about treatment, routine control and risk factors for complications scrining. Family medicine has an important role in the management of grade II hypertension and NYHA grade II heart failure, and requires the family support for the patient’s regular visit and obedient in take her medicines. [J Agromed Unila 2014; 1(2):114-118] Keywords: elderly women, grade II hypertension, NYHA grade II heart failure